CONTEXTUALISING ISLAMIC LAWS - Moh. Dahlan (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2018)
This paper by using the ijtihad paradigm of maqâshid al-syarî’ah of Jasser Audah and the descriptive-analytical approach, would like to emphasize that the role of religion and economic welfare are two things that cannot be separated. Although in practice these two things often face obstacles, especially in the matter of diversity in religious life because of the superficial ijtihad paradigm of Islamic law. Based on the contemporary paradigm that seeks to provide new criteria in the conception of qath’i al-dlilalah and dlanni al-dlilalah, it can be stated that the contemporary Islamic law paradigm that needs to be built must be based on (a) the development of citizens’ welfare Muslims, but also must be the same as non-Muslims because of that we need to carry out financial and economic reforms (al-ishlâh al-mâlî wa al-iqtishâdî); (b) protection of freedom of thought (hurriyah al-tafkîr) and freedom of religion (hurriyah al-i’tiqâd) is an important aspect that must be maintained to guarantee the peace and harmony of the nation’s life in the territory of Indonesia. Therefore, the religious and economic aspects must be prioritized for their protection and safety.